دراسة واقع الذّكاء التّسويقي في المصارف الخاصّة العاملة في الساحل السوري - نصور, ريزان; اسبر, سعيد; خليل, ولاء (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يهدف البحث إلى دراسة واقع الذّكاء التّسويقي (ذكاء العميل، ذكاء المنافس، مشاركة المعلومات التّسويقيّة بين الأقسام) في المصارف الخاصّة العاملة في السّاحل السّوري. اعتمدت الباحثة على المنهج الوصفي، وقامت بتطوير استبانة لجمع البيانات الأوّليّة عن مفردات عيّنة البحث، والّتي هي عبارة عن عيّنة ميّسرة من المدراء العاملين في المصارف الخاصّة في السّاحل السوري. تمّ توزيع 50 استبانة، استرد منها 39 صالحة للتحليل الإحصائي، وقد استخدم لتحليلها مجموعة من الأدوات الإحصائيّة الّتي يوفّرها البرنامج الإحصائي SPSS وأهمّها: المتوسط الحسابي، الأهميّة النسبيّة، واختبار T-test. فكانت أهم النّتائج: تتبنى المصارف محل الدّارسة بعد ذكاء العميل كأحد أهم مكوّنات الذّكاء التّسويقي بأهميّة نسبيّة بلغت (75.81%)، وبعد ذكاء المنافس كأحد أهم مكوّنات الذّكاء التّسويقي وبأهميّة نسبيّة بلغت (73.846%). كما تقدّمت الباحثة بمجموعة من التّوصيات، منها: على المصارف محل الدّراسة أن تعطي طابعاً أكثر رسميّة لنشاطات الذّكاء التّسويقي، وعليها أن تقوم بدراساتٍ تجريبيّة للحصول على معلوماتٍ عن العملاء، بالإضافة إلى ضرورة امتلاكها لملفاتٍ وتقاريرٍ مُحدّثة عن منافسيها في السّوق الماليّة؛ لتبقى على اطّلاعٍ دائمٍ بتحرّكاتهم، واستراتيجيّاتهم المُتّبعة. The research aims to study the reality of Marketing Intelligence (Customer Intelligence, Competitor Intelligence, Communicating Marketing Information among departments) in the private banks operating in the Syrian Coast. The research adapts the descriptive approach. A questionnaire has been developed to collect primary data from the research sample, which is a soft sample of 50 of Syrian Coast Private Banks' managers. 39 valid questionnaires have been returned, which then have been analyzed by using some Statistical tools provided by the statistical program SPSS, like: Means, relative importance, and T-test. The most important research's results are represented in:The Banks under study adapt customer intelligence as one of the most important components of marketing intelligence, with a relative importance reached to (75.81%), and Competitor Intelligence as one of the most important components of marketing intelligence, with a relative importance reached to (73.846%).The researcher also made a number of recommendations, including: The banks in question should give a more formal character to the activities of marketing intelligence, carry out pilot studies to obtain information about customers, and They should have update and detailed reports about competitors; to stay informed about their strategies and movements.